Lipid Lowering effect of Natural Honey in Comparison to Atorvastatin on Hyperlipidemic Rats (Journal of Dhaka Medical College, 2018)
Aims: The present study was performed to investigate the hypolipidaemic effect of natural honey in hyperlipidaemic rats. We also compared the hypolipidaemic effects of natural honey with a standard known hypolipidacmic agent, atorvastatin.Methods: At first the rats (n=42), were randomly divided into six groups. Each group composed of seven rats. Group A control group received normal diet, distilled water for 10 days. Group B hyperlipidemic group received normal diet olive oil (1.5inl) with cholesterol daily for 10 days. Group C received normal diet, distilled water. D, E & F. On the 11th day of experiment the final body weight was measured & blood was collected by cardiac puncture for the study of lipid profile.Result: Only cholesterol fed Group B and C rats gained body weights. Natural honey and atorvastatin treated group of rats. Group D, E, F lost body weights. These changes between the initial and final body weight were statistically significant (p